Make a decision surgery - Corrigan, Mark, MD (Wiley-Blackwell, 2010)
"Taking a non-linear, narrative approach and designed to be used in a 'role-playing' format, Make a Decision: Surgery allows the reader to take the role of the book's main character - a junior general surgeon on call in a busy hospital. Outcomes to clinical scenarios are based purely on the reader's decisions and actions. Each decision is scored and feedback is offered to the reader at the end of each scenario together with an exemplar response -- Provided by publisher.